Project Network of Multiplying Partners of Educational Sport: impact on the pedagogical practice (Research, Society and Development, 2021)
Education of Physical Education teachers, from 2013 to 2017, was the subject of the partnership established between the Institute of Sport & Education (IEE) and nine cities in the southern region of the state of Rio Grande do Sul (RS). This study aimed at sharing the experience of the Project Network of Multiplying Partners of Educational Sport (PRPMEE) in the state of RS, involving the implementation, execution and effectuation of Educational Sport practices, besides pointing out the impact of the proposed continuing education on the pedagogical practice of a Physical Education teacher intentionally selected in the city of Arroio Grande. The methodological steps were in accordance with a descriptive, qualitative research, and the information analysis was carried out with the use of Triviños’ technique of data triangulation. The instruments used for information collection were the following: semi-structured interview; observation of the pedagogical practice; pedagogical materials provided along the IEE modules of continuing education; and field journal. A reflective analysis of the results showed that PRPMEE continuing education process in RS, particularly in the city of Arroio Grande, was fundamental to effect qualified pedagogical practices in Physical Education classes, as the teacher participant followed what was learned in the education process proposed by IEE, by internalizing the methodology and putting it into practice in class.